Pengembangan Modul dan Trainer Mikrokontroler - Wildan Zulfikar Djunaedi; Bobi Kurniawan (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2020)
Abstract Teaching and learning process is a very important element in the world of Education, one's level of competence to compete in the world of work can be supported by a good teaching and learning process as well as adequate facilities. The latest technology has many benefits that are very useful for daily life such as microcontroller technology, wireless technology or IoT (Internet of Things). The design of the trainer is based on the needs of the Vocational School which includes basic modules and communication modules so that they can be used for more interactive programs. Testing basic modules such as LEDs, push buttons, servo motors, dc motors, stepper motors, relays, LCDs, sensors (distance, temperature and PIR) each program can run well, as well as communication modules that are tested using a desktop program run well. Feasibility testing is done by giving questionnaires to 12th grade vocational students, data processing is done using a Likert scale, from 3 categories given through the questionnaire for the aspect of